1988
DOI: 10.1901/jeab.1988.50-173
|View full text |Cite
|
Sign up to set email alerts
|

Self‐control: Teaching Tolerance for Delay in Impulsive Children

Abstract: We investigated a procedure to increase the selection of larger, more delayed reinforcers (i.e., more advantageous in the long run) over smaller immediate reinforcers, in an effort to increase a key aspect of self-control in children. Six preschoolers, including one comparison subject, identified by their teachers as impulsive, were preassessed and found consistently to select smaller immediate reinforcers over larger, more delayed ones. The teaching procedure consisted of gradually increasing the durations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
132
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 41 publications
10
132
0
4
Order By: Relevance
“…For the self-control sessions, the apparatus was identical to the apparatus used in previous research (Forzano & Logue, 1995;Forzano et al, 2003;Logue & Chavarro, 1992;Logue et al, 1996). The apparatus was a wooden box (76 cm wide × 80 cm high × 47 cm deep) with an open back (adapted from Schweitzer & Sulzer-Azaroff, 1988). On the front of the box was a picture of Mickey Mouse (see Figure 1).…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the self-control sessions, the apparatus was identical to the apparatus used in previous research (Forzano & Logue, 1995;Forzano et al, 2003;Logue & Chavarro, 1992;Logue et al, 1996). The apparatus was a wooden box (76 cm wide × 80 cm high × 47 cm deep) with an open back (adapted from Schweitzer & Sulzer-Azaroff, 1988). On the front of the box was a picture of Mickey Mouse (see Figure 1).…”
Section: Methods Participantsmentioning
confidence: 99%
“…In other words, both externally imposed and self-imposed delay tasks involve a choice component, but only self-imposed delay tasks involve sustaining that choice or inhibiting the response for the smaller, less delayed reinforcer (Reynolds & Schiffbauer, 2005). Precommitment procedures have been found to result in increases in self-control (Chelonis, Logue, Sheehy, & Mao, 1998;Schweitzer & Sulzer-Azaroff, 1988).…”
mentioning
confidence: 99%
“…In several areas of self-regulation, it has proved possible to train individuals in self-control, for example, teaching tolerance for delay to gain greater reward to preschoolers 137 and improving emotion and impulse control in school children. This has also proved a valuable approach in improving adherence to health interventions targeting increased physical activity, 138 fruit and vegetable consumption 139 and smoking cessation.…”
Section: Theoretical Perspectives On Factors Influencing Self-regulatmentioning
confidence: 99%
“…Schweitzer & Sulzer-Azaroff (1988) described one method whereby the delay is gradually increased for a larger reinforcer while the smaller reinforcer remains immediately available. Dixon and Cummins (2001) extended this research further by illustrating that self-control may be increased by establishing a history in which participants are gradually exposed to progressive delays, and are concurrently given the choice to engage in an intervening activity during that delay.…”
Section: Using a Time Timer Tm To Increase Appropriate Waiting Behavimentioning
confidence: 99%
“…It has been suggested that an adult human's increased preference for delayed, larger reinforcers may somehow be linked to their advanced verbal abilities (Schweitzer & Sulzer-Azaroff, 1988). This may explain why people with a limited verbal capacity experience difficulties in waiting for delayed reinforcement.…”
Section: Using a Time Timer Tm To Increase Appropriate Waiting Behavimentioning
confidence: 99%